Effects of environmental conditions on the lap shear strength of resistance-welded carbon fibre/thermoplastic composite joints. (1st October 2020) - Rohart, Vincent; Lebel, Louis Laberge; Dubé, Martine
Abstract: The objective of this study is to understand the influence of temperature and moisture on the lap shear strength (LSS) of carbon fibre/polyphenylene sulfide (CF/PPS) resistance-welded joints. The welded joints are conditioned at various levels of temperature and humidity and tested at temperatures ranging from 21 °C to 150 °C. Temperature is shown to have an effect on the LSS with a reduction of 26% at 82 °C and 61% at 150 °C (around 60 °C above the PPS Tg ), relative to room temperature. Moisture is shown to have little to no impact on the LSS, due to the semi-crystalline nature of PPS and its good resistance to water absorption. Observation of the joints' fracture surfaces shows a degradation of the fibre/matrix interface under severe environmental conditions and a failure mode involving both fibre/matrix and heating element/matrix debonding.